THE CORRELATION OF MICROSTRUCTURE, AND MECHANICAL PROPERTIES OF NOVEL Fe3O4-(AuTe2) –REINFORCED ALUMINIUM MATRIX COMPOSITE PRODUCED VIA RECRYSTALLIZATION ROUTE (FUDMA JOURNAL OF SCIENCES, 2023)
Aluminum Metal Matrix Composites (AMMC) have been becoming suitable materials for many devices in the application of various fields such as medical equipment, aircraft, electrical motors, overhead transmission lines, construction, etc. Aluminum was reinforced with the Fe3O4-(AuTe2) through the recrystallization process, hence, AMMC was successfully developed. The aim was to characterize the microstructure and phase patterns of the developed AMMC and compare it with conventional Aluminum as well as its thermos-mechanical characteristics. Physical, mechanical, and morphological properties of the composite and regular Al were examined. Based on the outcomes, the microstructural examination of the composite showed that the Al matrix had a sizable distribution of reinforcement components. Additionally shown was the creation of new phases, which significantly improved the strength and corrosion resistance of the composite. The influence of the reinforcement materials was found to have greatly enhanced the hardness tests. From 60 HRB for ordinary Al to 92.3 for AMMC, the hardness rose. Hence, after corrosion tests in an acidic solution (5% H2SO4 + H2O) hardness also increased from 41.1 HRB of the conventional Al to 52.8 HRB of the AMMC. Therefore, Corrosion resistance is improved by adding this reinforcement (Al- Fe3O4-(AuTe2) to the composite (lower corrosion rate). We then chose Al-5Fe3O4-10(AuTe2) as an optimal composite after comparing all the samples.
Keywords: Microstructure, solar thermal, corrosion behavior, hardness, recrystallization